2019
DOI: 10.1186/s40945-019-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Review of scoliosis-specific exercise methods used to correct adolescent idiopathic scoliosis

Abstract: Background Adolescent idiopathic scoliosis (AIS) refers to a spinal curvature of an unknown origin diagnosed in otherwise healthy children. A conservative treatment approach includes physiotherapy scoliosis-specific exercises (PSSE) with or without corrective bracing in preventing further spinal column deviation. However, several PSSE types have been developed to facilitate a positive patient outcome and/or preclude surgical remediation. Based on other reviews, there has been insufficient evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 22 publications
2
60
3
1
Order By: Relevance
“…Level II evidence (RCT) was considered the best methodology to answer intervention-related questions in a systematic review. However, considering the limited number of RCT in the most up-to-date reviews [33,49,51,52], prospective clinical control trials (CCT: Level III) were also analyzed in this study.…”
Section: Evidence Hierarchy and Methodological Appraisalmentioning
confidence: 99%
See 2 more Smart Citations
“…Level II evidence (RCT) was considered the best methodology to answer intervention-related questions in a systematic review. However, considering the limited number of RCT in the most up-to-date reviews [33,49,51,52], prospective clinical control trials (CCT: Level III) were also analyzed in this study.…”
Section: Evidence Hierarchy and Methodological Appraisalmentioning
confidence: 99%
“…Thus, the quality of enrolled studies in that review was relatively poor [49]. Another three systematic reviews enrolled studies between 2005 and 2017 and found insufficient and low-quality clinical trials showing effects of SSE on improving the scoliotic deformity [33,51,52]. One review confirmed the promising effects of the Schroth method in curve regression but had analyzed only four studies [51]; one review analyzed nine articles of which three (33%) did not use SSE and one (11%) was an outdated article published 15 years ago [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of the review is the lack of high-quality studies, which makes it di cult to extract adequate data to reach any rm conclusions. The previous systematic reviews (33,52), analyzed the same ve studies (35,37,41,45,48) included in our review, revealed a signi cant heterogeneity by statistical testing and concluded that no pooled effect sizes could be reliably reported. In addition, our review included ve more updated clinical trials that showed notable methodological heterogeneity: one CCT was conducted with a large sample size (n=99) but no comparative untreated controls (40); four studies, including one CCT (38) and three RCTs (36,46,47), were conducted with small sample sizes (n<50) which could mask variations and build up of systematic errors.…”
Section: Discussionmentioning
confidence: 80%
“…This review aimed to estimate the effect of SSE on scoliotic deformity improvement. Unlike the previous reviews (33,51,52), besides of reporting a reduction in Cobb angle, our review emphasized the true effect in terms of reductions beyond clinical measurement errors. The clinical standard for individual curve regression was reported to be >5° (55).…”
Section: Discussionmentioning
confidence: 96%